Spark the life of electricity and the electricity of life - Jorgensen, Timothy J. (Princeton University Press, 2021)
"A fresh look at electricity and its powerful role in life on EarthWhen we think of electricity, we likely imagine the energy humming inside our home appliances or lighting up our electronic devices-or perhaps we envision the lightning-streaked clouds of a stormy sky. But electricity is more than an external source of power, heat, or illumination. Life at its essence is nothing if not electrical.The story of how we came to understand electricity's essential role in all life is rooted in our observations of its influences on the body-influences governed by the body's central nervous system. Spark explains the science of electricity from this fresh, biological perspective. Through vivid tales of scientists and individuals-from Benjamin Franklin to Elon Musk-Timothy Jorgensen shows how our views of electricity and the nervous system evolved in tandem, and how progress in one area enabled advancements in the other. He explains how these developments have allowed us to understand-and replicate-the ways electricity enables the body's essential functions of sight, hearing, touch, and movement itself.Throughout, Jorgensen examines our fascination with electricity and how it can help or harm us. He explores a broad range of topics and events, including the Nobel Prize-winning discoveries of the electron and neuron, the history of experimentation involving electricity's effects on the body, and recent breakthroughs in the use of electricity to treat disease.Filled with gripping adventures in scientific exploration, Spark offers an indispensable look at electricity, how it works, and how it animates our lives from within and without"--